Shifting Echoes: Re-Evaluating Three Generations` Perspectives on Nicknames toward Bullying - Tur, Ajar Pradika Ananta; Daulay, Resneri; Farida, Hana (Bina Nusantara University, 2024)
Within the Mandailing community in Rokan Hulu, as the novelty, the research investigated the diverse viewpoints on nicknames that had developed throughout three generations (older people, millennials, and Generation Z), with a specific emphasis on the links between nicknames and bullying. These nicknames, which could be affectionate or insulting, could fuel or stop bullying. The researchers conducted an interview and a survey at Rokan Hulu, a suburban region in Sumatra, to gather qualitative data for the research. A survey was distributed to 40 individuals in Rokan Hulu. It is evident from the findings that attitudes have changed over time. Many individuals from older generations view nicknames as a form of endearment due to their perceived innocence and strong cultural heritage roots. On the other hand, younger generations, notably millennials and Generation Z, are becoming more aware of the potentially harmful effects that certain nicknames can have, particularly in connection with bullying and inclusion in social groups. People interpret and use language in a way that mirrors the broader societal and cultural changes occurring. By re-evaluating how different generations perceive nicknames, the research contributes significantly to a more in-depth comprehension of how shifting cultural norms influence linguistic practices and the social repercussions of those practices, particularly in the context of bullying.